Angiotensin‐converting enzyme gene polymorphism and digestive system cancer risk: A meta‐analysis based on 9656 subjects - Abdeahad, Hossein; Avan, Amir; Khazaei, Majid; Soleimanpour, Saman; Ferns, Gordon A.; Fiuji, Hamid; Ryzhikov, Mikhail; Bahrami, Afsane; Hassanian, Seyed Mahdi (Journal of cellular biochemistry, 2019)
The angiotensin‐converting enzyme (ACE) is the major regulator of the renin‐angiotensin system, and it has been reported that genetic polymorphisms at this locus are associated with risk in numerous types of human cancers. In the current meta‐analysis, we aimed to evaluate the association between the ACE Gene insertion/deletion (I/D) polymorphism (DD vs II) and digestive system cancer susceptibility. A total of 19 case‐control studies among 3722 patients with seven different types of cancer were included in this meta‐analysis. In the pooled analysis, the relationship between the ACE I/D polymorphism and digestive system cancer risk was not statistically significant (odds ratio [OR], 0.93; 95% confidence interval [CI], 0.68‐1.29; P = 0.65; random model). Furthermore, subgroup analyses by cancer type also did not reveal an association between ACE polymorphisms and colorectal cancer (OR, 1.14; 95% CI, 0.823‐1.58; P = 0.43; random effect model) and gastric cancer (OR, 0.79; 95% CI, 0.51‐1.22; P = 0.28; random effect model). These findings indicate that ACE polymorphisms in the digestive tract may still affect the survival of cancer patients, and future studies into the topic of effect of ACE on cancer prognosis are warranted. In the current meta‐analysis, we aimed to evaluate the association between the ACE Gene insertion/deletion (I/D) polymorphism (DD vs II) and digestive system cancer susceptibility. A total of 19 case‐control studies among 3722 patients with seven different types of cancer were included in this meta‐analysis. Our findings indicate that ACE polymorphisms in the digestive tract may still affect the survival of cancer patients, and future studies into the topic of effect of ACE on cancer prognosis are warranted.